Investigating Determinants of MSMEs Interest in Digital Zakat Payment - Kotranada Gadwa Mufid; Yuliati Yuliati (Journal of Enterprise and Development (JED), 2025)
Purpose: This study aims to identify the factors influencing the interest of micro, small, and medium enterprises (MSMEs) in adopting digital zakat payments, with a particular focus on the role of zakat in supporting local economic development.Method: A quantitative research design was employed, with the population comprising all MSMEs operating in Malang City. A purposive sampling technique was utilized, yielding a sample of 100 respondents. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) version 25.Result: The findings indicate that zakat literacy, convenience, and religiosity have a positive and significant effect on the interest in digital zakat payments. This suggests that a strong understanding of zakat, the ease of use offered by digital platforms, and individuals' levels of religiosity enhance the likelihood of utilizing these platforms for zakat contributions. In contrast, trust does not exert a significant influence on digital zakat payment interest, indicating potential concerns regarding the perceived reliability of digital platforms for zakat distribution. Furthermore, transparency has a negative effect, suggesting a lack of understanding regarding the openness and accountability of zakat institutions.Practical Implications for Economic Growth and Development: The study recommends that zakat institutions enhance transparency and user convenience in the management of digital zakat payments. Strengthening these aspects may lead to greater participation in zakat contributions, thereby fostering broader economic growth and development.